2019
DOI: 10.1111/bjh.15997
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin use on the outcomes of newly diagnosed diffuse large B‐cell lymphoma and follicular lymphoma

Abstract: Summary The diabetes mellitus (DM) drug metformin targets mechanistic/mammalian target of rapamycin and inhibits lymphoma growth in vitro. We investigated whether metformin affected outcomes of newly diagnosed diffuse large B‐cell (DLBCL, n = 869) and follicular lymphoma (FL, n = 895) patients enrolled in the Mayo component of the Molecular Epidemiology Resource cohort study between 2002 and 2015. Hazard ratios (HR) and 95% confidence intervals (CIs) adjusted for age, sex, body mass index, prognostic index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…However, in a retrospective review of 213 patients, 31 on metformin at presentation, no difference in outcome was identified 6 . A recent publication 25 identified no survival advantage in patients with newly diagnosed DLBCL or FL exposed to metformin at time of diagnosis. In our present cohort, 16% of the patients received metformin with no association between OS and any metformin exposure, or any time‐varying exposure impact.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a retrospective review of 213 patients, 31 on metformin at presentation, no difference in outcome was identified 6 . A recent publication 25 identified no survival advantage in patients with newly diagnosed DLBCL or FL exposed to metformin at time of diagnosis. In our present cohort, 16% of the patients received metformin with no association between OS and any metformin exposure, or any time‐varying exposure impact.…”
Section: Discussionmentioning
confidence: 97%
“…In a population-based case-control study and two large, retrospective analyses, there were no significant correlations between metformin use and disease progression or survival in patients with non-Hodgkin lymphoma (NHL) [ 75 , 76 , 77 ]. However, in a Taiwanese study using a database of over 600,000 newly diagnosed DM patients enrolled in the National Health Insurance database, metformin initiators consistently had a lower risk of NHL [ 78 ].…”
Section: Metformin In Cancermentioning
confidence: 99%
“…Although some reports indicated that metformin might improve outcomes of lymphoma patients, the results from the previous studies showed inconsistent. In a cohort study of newly diagnosed DLBCL (n = 869) and FL (n = 895) patients enrolled in the Mayo component of the Molecular Epidemiology Resource cohort study between 2002 and 2015, the results showed that use of metformin was not associated with improved outcomes in newly diagnosed DLBCL and FL [ 114 ]. Metformin has been repeatedly shown to regulate lipid metabolism, not only via its antidiabetic effect but also through the activation of adenosine monophosphate kinase (AMPK) which mediates the regulations of peroxisomal proliferator-activated receptor α (PPARα) and PPARγ [ 115 117 ].…”
Section: Lymphoma and Metabolic Disorders/diseasesmentioning
confidence: 99%